2020
DOI: 10.3390/app10176103
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Extraction Maximization and Enzymatic Synthesis of Biodiesel from Microalgae

Abstract: Microalgae has received overwhelming attention worldwide as a sustainable source for energy generation. However, the production of biofuel from microalgae biomass consists of several steps, of which lipid extraction is the most important one. Because of the nature of feedstock, extraction needs special attention. Three different methods were studied to extract algal oil from two different algae variant, Chlorella sp. and Spirulina sp. The highest percentage oil yield was obtained by ultrasonication (9.4% for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…Among all fatty acid methyl esters, palmitic acid methyl ester (PAME) was the most abundant in all the lipid extracts, followed by oleic and stearic methyl esters. Similar observations were made by Fattah et al (2020) who found FAME compositions obtained by enzymatic synthesis from Chlorella sp. and Spirulina sp., were mainly predominated by palmitic acid, followed by oleic and stearic methyl esters.…”
Section: Determination Of Fatty Acids Composition In the Lipid Fractionsupporting
confidence: 88%
“…Among all fatty acid methyl esters, palmitic acid methyl ester (PAME) was the most abundant in all the lipid extracts, followed by oleic and stearic methyl esters. Similar observations were made by Fattah et al (2020) who found FAME compositions obtained by enzymatic synthesis from Chlorella sp. and Spirulina sp., were mainly predominated by palmitic acid, followed by oleic and stearic methyl esters.…”
Section: Determination Of Fatty Acids Composition In the Lipid Fractionsupporting
confidence: 88%
“…The chemical catalysis process for producing biodiesel consumes energy and creates undesirable by-products, such as soaps and polymeric pigments, which impede product separation from glycerol and di-and monoacylglycerols, which can be eliminated using enzymatic catalysis [138]. Biodiesel production by enzymatic catalysis has emerged as the most promising new technology [139][140][141]. This is evidenced by the intensive publications on enzymatic transesterification of lipids (oils/fats) in the last two decades [142][143][144][145][146].…”
Section: Enzymatic Catalysismentioning
confidence: 99%
“…It has been reported that Spirulina spp. has a total lipid content in the range of 6.4–14.3% DW [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%